Akibat Hukum Berlakunya Penghapusan Legalisasi Atas Dokumen Publik Asing Terhadap Kewenangan Legalisasi Notaris - Randyarsa Nurindra Irawan; Ananda Putri Pratama; Mella Fitriyatul Hilmi; Felicia Dzurriyatul Auliya (Fakultas Hukum Universitas Airlangga, 2024)
Apostille legalization is the process of certifying an official's signature, stamp attestation, and/or official seal in a document that has been sought based on verification. Indonesia becomes a party to the Convention Abolishing the Requirement of Legalization for Foreign Public Documents by enacting Presidential Regulation Number 2 of 2021 concerning the Ratification of the Convention on the Elimination of Legalization Requirements for Foreign Public Documents. Following this, the Minister of Law and Human Rights Number 6 of 2022 was introduced as an implementing rule. According to the rule, the Minister executes the Apostille through the Republic of Indonesia's Director General of Law and Human Rights. This study examines the legal ramifications of Presidential Regulation regarding the Elimination of Legalization Requirements for Foreign Public Documents against Notary regulation, specifically with regard to Article 15 Paragraph 2 Point A. Since notaries have the right to legalize under the Notary Position Regulation, the existence of a policy that eliminates legalization requirements sidelines and deprioritizes the role of notaries in the process of attestation of foreign public documents. This article's goal is to assess legal changes related to policy renewals that aim to do away with Indonesia's need to authorize foreign public documents in light of Presidential Regulation. Conceptual and statute-based normative juridical research methodologies are used in this work. Due to this issue, notaries are not permitted to legalize foreign documents and are therefore not involved in the apostille process. Notaries should be competent parties to legalize foreign public documents, because parties will deal directly with notaries. Notaries can also play a role in legalizing foreign public documents, provided that the notary is still given permission in the form of appointment of special positions related to legalizing foreign public documents